Adipocyte-specific Steap4 deficiency reduced thermogenesis and energy expenditure in mice - Han Wang; Lizi Zhang; Xing Chen; Lingzi Hong; Junjie Zhao; Wen Qian; Lam Khue Pham; Belinda Willard; Xiaoxia Li; Katarzyna Bulek; Xiao Li (iScience)
Summary: Six-transmembrane protein of prostate 4 (Steap4), highly expressed in adipose tissue, is associated with metabolic homeostasis. Dysregulated adipose and mitochondrial metabolism contributes to obesity, highlighting the need to understand their interplay. Whether and how Steap4 influences mitochondrial function, adipocytes, and energy expenditure remain unclear. Adipocyte-specific Steap4-deficient mice exhibited increased fat mass and severe insulin resistance in our high-fat diet model. Mass spectrometry identified two classes of Steap4 interactomes: mitochondrial proteins and proteins involved in splicing. RNA sequencing (RNA-seq) analysis of white adipose tissue demonstrated that Steap4 deficiency altered RNA splicing patterns with enriched mitochondrial functions. Indeed, Steap4 deficiency impaired respiratory chain complex activity, causing mitochondrial dysfunction in white adipose tissue. Consistently, brown adipocyte-specific Steap4 deficiency impaired mitochondrial function, increased brown fat whitening, reduced energy expenditure, and exacerbated insulin resistance in a high-fat model. Overall, our study highlights Steap4’s critical role in modulating adipocyte mitochondrial function, thereby controlling thermogenesis, energy expenditure, and adiposity.